PERAN GURU DALAM PENERAPAN PROGRAM LITERASI SELAMA MASA PANDEMI COVID-19 DI SEKOLAH DASAR GUGUS V KECAMATAN GUNUNGSARI - Fitria Pramitha Putri; Asrin Asrin; Heri Setiawan; Awal Nur Kholifatur Rosyidah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the role of teachers used in implementing literacy programs during the Covid-19 pandemic. Teachers act as trainers in the implementation of literacy programs, besides that teachers also act as adapters and developers so that teachers are not only curriculum implementers but teachers can align the curriculum and have the authority to design the curriculum by determining the strategies used to measure the level of success. This type of research is quantitative research with the research design used is survey research. The results of the instrument test with construct validity through expert opinion found that there were several statements that had to be corrected in the language structure so that this instrument could be declared worthy of taking data on the teacher's role in implementing literacy programs. The subjects of the study were class teachers in Cluster V Gunungsari, West Lombok as many as 31 people. The results obtained are the implementation of the literacy literacy program has a percentage of 82.80 percent, the implementation of the numeracy literacy program has a percentage of 82.73 percent, the implementation of the scientific literacy program has a percentage of 80.11 percent, and the application of digital literacy programs has a percentage of 87.43 percent. It can be seen that teachers are more involved in implementing digital literacy programs during the Covid-19 pandemic, this is because digital literacy programs have a higher percentage than other literacy programs. This means that teachers also implement literacy, scientific literacy, and numeracy literacy programs, but the implementation is through digital media because during this pandemic there are obstacles to face-to-face learning.